PELAKSANAAN PERJANJIAN PENDANAAN DALAM PERJANJIAN BANGUN BAGI DI KELURAHAN TANJUNG SARI MEDAN (RELEVASINYA DENGAN TANGGUNG JAWAB NOTARIS) - JULIANITA PERANGIN - ANGIN (PREMISE LAW JURNAL, 2017)
Build-share contract is a contract which comes from people ’s need because of the rapid development of business law. It is made between developers and land owners, and it is usually preceded by financing agreement among developers who gather an amount of financing for buying land and constructing a real estate according to their agreement. The research used normative juridical method. The nature of the research was descriptive analytic which was aimed to describe, explain, and analyze the research problems and found the answers and the solution. The result of the research showed that the implementation of financing agreement in the build-share contract in the construction of the real estate at Kelurahan Tanjung Sari, Jalan Setia Budi, Medan, was started by making a financing agreement by four developers: developer A shared 30%, developer B shared 40%, developer C shared 20%, and developer D shared 10% of the total capital for constructing a real estate on the land area of 10,729 m2. The Notary’s liability in the dispute due to the default of one of the parties in constructing the real estate at Kelurahan Tanjung Sari was only ethic and moral responsibility by giving legal advice to the conflicting parties so that the dispute was settled by negotiation.Keywords: Financing Agreement, Build-Share Contract, Default